A male-female mathematical model of human papillomavirus (HPV) in African American population - Najat Ziyadi (Mathematical Biosciences and Engineering)
We introduce mathematical human papillomavirus (HPV) epidemic models (with and without vaccination) for African American females (AAF) and African American males (AAM) with 'fitted' logistic demographics and use these models to study the HPV disease dynamics. The US Census Bureau data of AAF and AAM of 16 years and older from 2000 to 2014 is used to 'fit' the logistic demographic models. We compute the basic reproduction number, $\mathcal{R}_0$ , and use it to show that $\mathcal{R}_0$ is less than 1 in the African American (AA) population with or without implementation of HPV vaccination program. Furthermore, we obtain that adopting a HPV vaccination policy in the AAF and AAM populations lower $\mathcal{R}_0$ and the number of HPV infections. Sensitivity analysis is used to illustrate the impact of each model parameter on the basic reproduction number.